The control region of the pdu/cob regulon in Salmonella typhimurium. - Chen, P (1994)
The pdu operon encodes proteins for the catabolism of 1,2-propanediol; the nearby cob operon encodes enzymes for the biosynthesis of adenosyl-cobalamin (vitamin B12), a cofactor required for the use of propanediol. These operons are transcribed divergently from distinct promoters separated by several kilobases. The regulation of the two operons is tightly integrated in that both require the positive activator protein PocR and both are subject to global control by the Crp and ArcA proteins. We have determined the DNA nucleotide sequences of the promoter-proximal portion of the pdu operon and the region between the pdu and cob operons. Four open reading frames have been identified, pduB, pduA, pduF, and pocR. The pduA and pduB genes are the first two genes of the pdu operon (transcribed clockwise). The pduA gene encodes a hydrophobic protein with 56% amino acid identity to a 10.9-kDa protein which serves as a component of the carboxysomes of several photosynthetic bacteria. The pduF gene encodes a hydrophobic protein with a strong similarity to the GlpF protein of Escherichia coli, which facilitates the diffusion of glycerol. The N-terminal end of the PduF protein includes a motif for a membrane lipoprotein-lipid attachment site as well as a motif characteristic of the MIP (major intrinsic protein) family of transmembrane channel proteins. We presume that the PduF protein facilitates the diffusion of propanediol. The pocR gene encodes the positive regulatory protein of the cob and pdu operons and shares the helix-turn-helix DNA binding motif of the AraC family of regulatory proteins. The mutations cobR4 and cobR58 cause constitutive, pocR-independent expression of the cob operon under both aerobic and anaerobic conditions. Evidence that each mutation is a deletion creating a new promoter near the normal promoter site of the cob operon is presented.